propriedades estruturais e eletrônicas de nanofilmes de TiO2anatase: Cálculos B3LYP-d∗ EM sistemas periódicos bidimensionais - Albuquerque, Anderson R. [UNESP]; Santos, Iêda M. G.; Sambrano, Júlio R. [UNESP] (My University, 2014)
STRUCTURAL AND ELECTRONIC PROPERTIES OF ANATASE TiO2THIN FILMS: PERIODIC B3LYP-D* CALCULATIONS IN 2D SYSTEMS. Structural and electronic properties of titanium dioxide (TiO2) thin films, in anatase phase, were investigated using periodic 2D calculations at density functional theory (DFT) level with B3LYP hybrid functional. The Grimme dispersion correction (DFT/B3LYP-D*) was included to better reproduce structural features. The electronic properties were discussed based on the band gap energy, and proved dependent on surface termination. Surface energies ranged from 0.80 to 2.07 J/m2, with the stability orders: (101) > (100) > (112) > (110) ~ (103) > (001) > (111), and crystal shape by Wulff construction in accordance with experimental data.
Stuctural and electronic properties of anatase TiO2 thin films: Periodic B3LYP-D* calculations in 2D systems